Activation of AMPK-SIRT3 signaling is chondroprotective by preserving mitochondrial DNA integrity and function - Chen, L.-Y.; Wang, Y.; Terkeltaub, R.; Liu-Bryan, R. (Osteoarthritis and cartilage, 2018)
In osteoarthritis (OA), articular chondrocytes manifest mitochondrial damage, including mitochondrial DNA 4977-bp (mtDNA4977) deletion that impairs mitochondrial function. OA chondrocytes have decreased activity of AMPK, an energy biosensor that promotes mitochondrial biogenesis. Here, we tested if pharmacologic AMPK activation, via downstream activation of predominately mitochondrially localized sirtuin 3 (SIRT3), reverses existing decreases in mitochondrial DNA (mtDNA) integrity and function in human OA chondrocytes and limits mouse knee OA development. We assessed mtDNA integrity and function including the common mtDNA4977 deletion and mtDNA content, mitochondrial reactive oxygen species (mtROS) generation, oxygen consumption and intracellular ATP levels. Phosphorylation of AMPKα, expression and activity of SIRT3, acetylation and expression of the mitochondrial antioxidant enzyme SOD2 and DNA repair enzyme 8-oxoguanine glycosylase (OGG1), and expression of subunits of mitochondrial respiratory complexes were examined. We assessed effect of pharmacologic activation of AMPK on age-related spontaneous mouse knee OA. The mtDNA4977 deletion was detected in both OA chondrocytes and menadione-treated normal chondrocytes, associated with increased mtROS, decreased SIRT3, and increased acetylation of SOD2 and OGG1. AMPKα1 deficient chondrocytes exhibited significantly reduced SIRT3 activity. AMPK pharmacologic activation attenuated existing mtDNA4977 deletion and improved mitochondrial functions in OA chondrocytes via SIRT3 by reducing acetylation and increasing expression of SOD2 and OGG1, and limited aging-associated mouse knee OA development and progression. AMPK activation, via SIRT3, limits oxidative stress and improves mtDNA integrity and function in OA chondrocytes. These effects likely contribute to chondroprotective effects of AMPK activity.